Comparative efficacy and safety of acetaminophen, topical and oral non-steroidal anti-inflammatory drugs for knee osteoarthritis: evidence from a network meta-analysis of randomized controlled trials and real-world data. Issue 9 (September 2021) - Zeng, C.; Doherty, M.; Persson, M.S.M.; Yang, Z.; Sarmanova, A.; Zhang, Y.; Wei, J.; Kaur, J.; Li, X.; Lei, G.; Zhang, W.
Summary: Objective: Current global guidelines regarding the first-line analgesics (acetaminophen, topical or oral non-steroidal anti-inflammatory drugs [NSAIDs]) for knee osteoarthritis remain controversial and their comparative risk–benefit profiles have yet to be adequately assessed. Design: Pubmed, Embase, Cochrane Library, and Web of Science were searched from database inception to March 2021 for randomized controlled trials (RCTs) comparing acetaminophen, topical NSAIDs and oral NSAIDs directly or indirectly in knee osteoarthritis. Bayesian network meta-analyses were conducted. A propensity-score matched cohort study was also conducted among patients with knee osteoarthritis in The Health Improvement Network database. Results: 122 RCTs (47, 113 participants) were networked. Topical NSAIDs were superior to acetaminophen (standardized mean difference [SMD] = −0.29, 95% credible interval [CrI]: −0.52 to −0.06) and not statistically different from oral NSAIDs (SMD = 0.03, 95% CrI: −0.16 to 0.22) for function. It had lower risk of gastrointestinal adverse effects (AEs) than acetaminophen (risk ratio [RR] = 0.52, 95%CrI: 0.35 to 0.76) and oral NSAIDs (RR = 0.46, 95%CrI: 0.34 to 0.61) in RCTs. In real-world data, topical NSAIDs showed lower risks of all-cause mortality (hazard ratio [HR] = 0.59, 95% confidence interval [CI]: 0.52 to 0.68), cardiovascular diseases (HR = 0.73, 95%CI: 0.63 to 0.85) and gastrointestinal bleeding (HR = 0.53, 95%CI: 0.41 to 0.69) than acetaminophen during the one-year follow-up ( n  = 22, 158 participants/group). A better safety profile was also observed for topical than oral NSAIDs ( n  = 14, 218 participants/group). Conclusions: Topical NSAIDs are more effective than acetaminophen but not oral NSAIDs for function improvement in people with knee osteoarthritis. Topical NSAIDs are safer than acetaminophen or oral NSAIDs in trials and real-world data.